Penurunan hidrograf satuan dengan data hujan harian - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Pengabdian Kepada Masyarakat UGM, 1998)
ABSTRACT The unit hydrograph method is one of flood estimation methods commonly used for design flood estimation. A number of problems emerges in the application of the unit hydrograph method, especially in Indonesia, such as lack of automatic rainfall data. Unit hydrograph derivation using daily rainfall data and alternating block method rainfall distribution in two selected catchments at Cimanuk river basin produce relatively small bias compare with unit hydrograph derived based on automatic rainfall data. Moreover, unit hydrographs derived using daily rainfall data yield slightly better results than synthetic unit hydrograph.